Effects of Additivation During MgO Calcination on Properties of MgO Powders and Magnesium Phosphate Cements - D.V. Ribeiro; G.R. Paula; M.R. Morelli (Materials Research, 2023)
Magnesium phosphate cement are materials prepared by reacting magnesium oxide with water-soluble phosphates such as mono-ammonium dihydrogen phosphate, which solidified at ambient temperature through the formation of hydrated phases in the material. However, MgO has a high reactivity and requires calcination to reduce its surface area, facilitating the practical application of magnesium phosphate cement. Because it is a process with large energy consumption, the sintering cost is very high when implemented at a large scale. Since the final stages of solid-state reaction are rarely reached, the addition of some components is beneficial from a calcination point of view, as they can lead to the formation of low melting liquid phases. In this study, effects of the inorganic activation of MgO on the properties of cements in terms of phase formation, microstructure, setting time, pore size distribution and mechanical properties were evaluated. The additivation considerably improved the properties of MgO powders, and Na2O-PbO-SiO2-Bi2O3-B2O3 was the most efficient additive to reduce de BET surface area (about 5-6 times). Cements produced using doped MgO without calcination at high temperatures or the use of higher levels of retarding and dispersing additives, showed better physical (porosity approximately 5 times lower and density approximately 38% higher) and mechanical properties (approximately 9 times higher) than the pastes produced with MgO calcined without additives (traditional method).